Parallel subfunctionalisation of PsbO protein isoforms in angiosperms revealed by phylogenetic analysis and mapping of sequence variability onto protein structure - Duchoslav, Miloš; Fischer, Lukáš (BMC plant biology, 2015)
BACKGROUND: PsbO, the manganese-stabilising protein, is an indispensable extrinsic subunit of photosystem II. It plays a crucial role in the stabilisation of the water-splitting Mn4CaO5 cluster, which catalyses the oxidation of water to molecular oxygen by using light energy. PsbO was also demonstrated to have a weak GTPase activity that could be involved in regulation of D1 protein turnover. Our analysis of psbO sequences showed that many angiosperm species express two psbO paralogs, but the pairs of isoforms in one species were not orthologous to pairs of isoforms in distant species. RESULTS: Phylogenetic analysis of 91 psbO sequences from 49 land plant species revealed that psbO duplication occurred many times independently, generally at the roots of modern angiosperm families. In spite of this, the level of isoform divergence was similar in different species. Moreover, mapping of the differences on the protein tertiary structure showed that the isoforms in individual species differ from each other on similar positions, mostly on the luminally exposed end of the β-barrel structure. Comparison of these differences with the location of differences between PsbOs from diverse angiosperm families indicated various selection pressures in PsbO evolution and potential interaction surfaces on the PsbO structure. CONCLUSIONS: The analyses suggest that similar subfunctionalisation of PsbO isoforms occurred parallelly in various lineages. We speculate that the presence of two PsbO isoforms helps the plants to finely adjust the photosynthetic apparatus in response to variable conditions. This might be mediated by diverse GTPase activity, since the isoform differences predominate near the predicted GTP-binding site.
Keywords: Protein Isoforms; sekundární struktura proteinů; Protein Structure, Tertiary; Genes, Plant; sekvence aminokyselin; Models, Molecular; fotosystém II (proteinový komplex); Open Reading Frames; Amino Acid Substitution; Photosystem II Protein Complex; substituce aminokyselin; rostlinné geny; molekulární modely; Protein Structure, Secondary; protein - isoformy; Amino Acid Sequence; fylogeneze; otevřené čtecí rámce; Species Specificity; druhová specificita; aminokyseliny; Phylogeny; terciární struktura proteinů; Magnoliopsida; Amino Acids